¿El fin de la autonomía? Los poderes y el INE en tiempos del presidente López Obrador - Prud'homme , Jean-François (El Colegio de México A.C., 2025)
This article examines the institutional conflict between the Executive and Legislative branches and Mexico’s National Electoral Institute (INE, in Spanish) during the period of President Andrés Manuel López Obrador’s administration, with a particular focus on the autonomy of the electoral authority. The analysis is framed within the perspective of democratic erosion, defined by Nancy Bermeo as the “state-led debilitation or elimination of the political institutions sustaining an existing democracy.” By tracing the evolution of this conflict at its different stages, the article highlights the strategies employed by the involved actors and the mobilization of resources at their disposal, whether administrative, legal, legislative, political, or discursive.